2016
DOI: 10.1016/j.antiviral.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genetic diversity has minimal impact on sensitivity of the viral ribonuclease H to inhibitors

Abstract: Hepatitis B virus (HBV) causes hepatitis, cirrhosis, liver failure, and liver cancer, but the current therapies that employ either nucelos(t)ide analogs or (pegylated)interferon α do not clear the infection in the large majority of patients. Inhibitors of the HBV ribonuclease H (RNaseH) that are being developed with the goal of producing anti-HBV drugs are promising candidates for use in combination with the nucleos(t)ide analogs to improve therapeutic efficacy. HBV is genetically very diverse, with at least 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…There were no differences in pretreatment human albumin levels among the four groups by a one-way ANOVA with the Dunnets’ post-hoc test. Genotype C was employed in this study rather than genotype A which was used in the preliminary study because we had preliminary data indicating that RNaseH inhibitors from these chemical classes could inhibit HBV from multiple genotypes (Lu et al, 2016). Using genotype A in the preliminary experiment and genotype C in the primary efficacy study allowed us to directly test that hypothesis in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences in pretreatment human albumin levels among the four groups by a one-way ANOVA with the Dunnets’ post-hoc test. Genotype C was employed in this study rather than genotype A which was used in the preliminary study because we had preliminary data indicating that RNaseH inhibitors from these chemical classes could inhibit HBV from multiple genotypes (Lu et al, 2016). Using genotype A in the preliminary experiment and genotype C in the primary efficacy study allowed us to directly test that hypothesis in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Recently we identified HBV RNaseH inhibitors in three chemical families that block HBV replication in cell culture (Cai et al, 2014; Edwards et al, 2017; Lomonosova et al, 2017a; Lu et al, 2015; Tavis et al, 2013a; Tavis and Lomonosova, 2015). We found that these inhibitors are equally effective against RNaseH enzymes from multiple isolates of HBV genotypes B, C, and D, implying that HBV’s high genetic diversity is unlikely to be a barrier to drug development (Lu et al, 2016). We also found that combinations of two RNaseH inhibitors from different chemical classes (α-hydroxytropolones (αHTs) and N-hydroxyisoquinolinediones (HIDs)) with the NA lamivudine or with each other synergistically inhibited HBV replication in cell culture (Lomonosova et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…HBV is a genetically diverse virus, with 8 to 10 genotypes that differ by Ն8% at the nucleotide level (51). Our studies were done with a genotype D isolate, but it is probable that our conclusions will apply to other genotypes as well for two reasons.…”
Section: Discussionmentioning
confidence: 98%
“…These compounds inhibit the HBV RNaseH in biochemical assays and cause accumulation of RNA:DNA heteroduplexes in viral capsids, confirming they target the RNaseH [6,9]. The RNaseH inhibitors repress HBV RNaseHs from three genotypes, indicating that HBV's high genetic diversity is unlikely to complicate drug development [13]. The inhibitors are synergistic with the nucleoside analog drug Lamivudine and additive with the experimental HBV capsid protein assembly modifier Hap12 without enhancing cytotoxicity [10,14].…”
Section: The Rnaseh As a Drug Targetmentioning
confidence: 97%